Proses Gasifikasi berbagai Jenis Biomassa pada Gasifier Downdraft - Aktawan, Agus (Universitas Ahmad Dahlan, 2015)
Biomass gasification is an endothermic reaction process for converting biomass into syngas. Gasification occurs at high temperatures with limited oxygen. Knowing the temperature profile of biomass gasification wood charcoal, coconut shell charcoal and coconut shell, rice husk and woodchip and seek optimal results from gasification of biomass are the purpose of the research. Research start by ignite the biomass in the gasifier, the air flows by blower and the syngas came out after the filter. Research variabel are variation of biomass types mentioned above. Observations were made up until the biomass in the gasifier did not produce syngas, characterized by gas results could not burn. The results of the temperature profile from gasification of various biomass shows that the syngas appeared in the early minutes (2 minutes until the 5th) on the gasification, such as gasification coconut shell, woodchip and rice husk. Syngas of coconut shell charcoal is 2,825% w/w of biomass and can burn for 19 minutes and resulted in 1,92% ash and 29,57% charcoal.